Identifing Insulators in Arabidopsis thaliana - Gandorah, Batool (Université d'Ottawa / University of Ottawa, 2012)
In transgenic research the precise control of transgene expression is crucial in order to obtain transformed organisms with expected desirable traits. A broad range of transgenic plants use the constitutive cauliflower mosaic virus (CaMV) 35S promoter to drive expression of selectable marker genes. Due to its strong enhancer function, this promoter can disturb the specificity of nearby eukaryotic promoters. When inserted immediately downstream of the 35S promoter in transformation vectors, special DNA sequences called insulators can prevent the influence of the CaMV35S promoter/enhancer on adjacent tissue-specific promoters for the transgene. Insulators occur naturally in organisms such as yeasts and animals but few insulators have been found in plants. Therefore, the goal of this study is to identify DNA sequences with insulator activity in Arabidopsis thaliana. A random oligonucleotide library was designed as an initial step to obtain potential insulators capable of blocking enhancer-promoter interactions in transgenic plants. Fragments from this library with insulator activity were identified and re-cloned into pB31, in order to confirm their activity. To date, one insulator sequence (CLO I-3) has been identified as likely possessing enhancer-blocking activity. Also, two other oligonucleotide sequences (CLO II-10 and CLO III-78) may possess insulator activity but more sampling is needed to confirm their activity. Further studies are needed to validate the function of plant insulator(s) and characterize their associated proteins.
Keywords: Arabidopsis thaliana; Insulators; CaMV 35S enhancer/promoter